Avaliação de catalisadores à base de platina-paládio suportados em carbono para a oxidação de etanol em eletrólitos ácido e básico - Carvalho, Leandro Lima (2018)
The management of the world energy matrix needs to be rethought, and in this context, the energy sector is, over all, the focus of this discussion, and the present, depends more and more on new strategies for energy production. In this way, the advances in the development of technologies about alternative sources of energy generation called Fuel Cells, mainly the electrochemical devices which working with ethanol as fuel (DEFCs). This work, the carbon supported Pt/C; Pd/C; Pt75Pd25/C; Pt75(PdOx)25/C; Pt50Pd50/C e Pt50(PdOx)50/C electrocatalysts with 20wt% of metal on carbon were prepared by fast reduction with sodium borohydride (NaBH4) followed by thermal treatment. The materials were characterized by X-ray diffraction (XRD) Transmission electron microscopy (TEM) and High resolution transmission electron microscopy (HRTEM), x-ray energy dispersive spectroscopy (EDS), cyclic voltammetry (VC) and Chronoamperometry. The EDS spectra showed e, experimental compositions of electrocatalysts are close to nominal, which suggest, high efficiency of the redactor agent BH4(aq) - /OH- (aq) for reducing the ions Pt+4 (H2PtCl6.6H2O) and Pd+2 (PdCl2.6H2O). The XRD analysis indicate the nanoparticle arrangement of the Platinum-Paladium with different content results in crystalline structure on carbon support, and the peaks assigned to Pt75(PdOx)25/C and Pt50(PdOx)50/C were observed indicating oxide formation from metal precursors Pt75Pd25/C e Pt50Pd50/C by thermal treatment method. The micrographs HRTEM showed homogenies particle size distribution on high area Vulcan XC-72 Carbon support. The particle size were determined as the maximum of Gaussian distribution of Pt/C; Pd/C e PtxPdy/C which showed electrochemical activity toward ethanol oxidation reaction in both, acid and alkaline, electrolyte. The exception is Pd in acid media. Moreover, the materials Pt75Pd25/C; Pt75(PdOx)25/C; Pt50Pd50/C e Pt50(PdOx)50/C with high Pd content, showed more better performance for ethanol oxidation reaction in alkaline media, with high anodic current density registered in the cyclic voltammetry and chronoamperometry experiments, in comparison with Pd/C e Pt/C catalysts.